Community-based Enterprise as a Strategy for Development in Aboriginal Communities: Learning from Essipit’s Forest Enterprises - Beaudoin, Jean-Michel; Bouthillier, Luc; Bulkan, Janette; Nelson, Harry; Wyatt, Stephen (Journal of Aboriginal Economic Development, 2015)
There is growing evidence of the socioeconomic importance of Aboriginal forest enterprises. Aboriginal groups that decide to opt-in to the market economy still face significant challenges. One critical challenge is the matter of harmonizing community members' needs with market requirements. Drawing on a case study in the Essipit Innu First Nation in Canada, this paper examines the successes attained by an Aboriginal community-based enterprise (ACBE) strategy in enhancing sustainable local development. Our results indicate that the community had access to, and expanded, human, natural, social and financial capital. Findings also show that Essipit defines success not only in economic terms, but also through a wider array of goals. This research shows a path towards Aboriginal economic success. It emphasizes the importance of developing a model that is integrated into the community and the local culture.